Kisah Transfigurasi Yesus dan Teologi Markus: Perspektif Injil Sinoptik (International Forum of Researchers and Lecturers, 2025)
This research examines the transfiguration of Jesus in the Synoptic Gospels, with particular emphasis on the theological distinctiveness of the Gospel of Mark. The study employs a qualitative method using a literature review approach, focusing on narrative analysis, textual comparison, and theological reflection. The analysis shows that although Matthew, Mark, and Luke present the transfiguration event, each Gospel offers distinctive features in wording, narrative structure, and theological emphasis. Mark presents the transfiguration in a concise form, portraying Jesus as the messianic Son of God and as a prophet like Moses, while highlighting the apocalyptic and symbolic aspects of this divine encounter. From Mark’s perspective, the transfiguration serves as a prefiguration of Jesus’ resurrection and a revelation of His messianic identity, which in the Greco-Roman context may be understood as apotheosis—the elevation of a human into divinity. This study affirms that the transfiguration in Mark is not only a historical event but also a theological event that encompasses eschatological and christological dimensions, as well as a reflection on divine hiddenness. In conclusion, the transfiguration is understood as a manifestation of Jesus’ hidden glory within suffering, confirming that the path to resurrection and glory must pass through the cross. This article contributes to biblical and theological studies by demonstrating how Mark articulates a unique christology, one that remains relevant for contemporary Christian faith and opens avenues for further exploration through apocalyptic theology and scriptural intertextuality.